2020
DOI: 10.1038/s41551-020-00642-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of antibody avidities and accurate detection of SARS-CoV-2 antibodies in serum and saliva on plasmonic substrates

Abstract: Accurate assays for the detection of antibodies to SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) are essential for the control of the COVID-19 (coronavirus disease 2019) pandemic. Here, we report antibody and antibody-avidity assays, relying on near-infrared-fluorescence amplification by nanostructured plasmonic gold substrates, for the simultaneous detection of antibodies to the S1 subunit of the spike protein and to the receptor binding domain of SARS-CoV-2 in human serum and saliva, and for q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 55 publications
5
81
0
1
Order By: Relevance
“…The repeated findings on low avidity of IgG directed towards SARS‐CoV‐2 antigens, even several months after onset of clinical symptoms 11,13,14,19–21 ; are unique in viral serodiagnostics so far. Though Luo et al 12 stated that there was a strong correlation between avidity or IgG towards RBD and days after onset of symptoms, their findings are also supporting the findings on low avidity of IgG towards SARS‐CoV‐2 antigens, as the authors had used the very low concentration of 3 M urea in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The repeated findings on low avidity of IgG directed towards SARS‐CoV‐2 antigens, even several months after onset of clinical symptoms 11,13,14,19–21 ; are unique in viral serodiagnostics so far. Though Luo et al 12 stated that there was a strong correlation between avidity or IgG towards RBD and days after onset of symptoms, their findings are also supporting the findings on low avidity of IgG towards SARS‐CoV‐2 antigens, as the authors had used the very low concentration of 3 M urea in their study.…”
Section: Discussionmentioning
confidence: 99%
“… Strömer et al, 2020a , Strömer et al, 2020b also describe predominantly occurring low avidity IgG towards SARS-CoV-antigens, while using a prototype version as well as the final version of the same assay system as used by us. Liu et al 2020 reported that IgG towards S1 and RBD of SARS-CoV-2 showed avidity indices below 0.3 within the first 45 days after onset of disease, except for one serum with an avidity index of about 0.8 before day 10.…”
Section: Incomplete Avidity Maturation Of Igg After Natural Infectionmentioning
confidence: 96%
“…In a review of seven other newly reported COVID-19 antibody testing technologies, several were found to be semi-quantitative( Mairesse et al, 2020 ; Soleimani et al, 2021 ), while others have narrow dynamic range or lack clinically validation ( Table S2 ). ( Tan et al 2020 ; Shaw et al 2020 ; Roy et al 2020 ; Liu et al 2020 ; Dzimianski et al 2020 ) In general, we believe that the DNA-assisted nanopore assay can simultaneously quantify SARS-CoV-2 antibodies with higher accuracy and larger dynamic range, while correlating with results from the “gold standard diagnostic technology” ELISA.…”
Section: Discussionmentioning
confidence: 98%